Elements of philosophy in Chinua Achebe’s Things Fall Apart (1958) - Ansah, Richard; Segbefia, Michael (Research Journal in Advanced Humanities, 2021)
An examination of the position of any school of thought on the nature of African philosophy will lead one to the realization that traditional African cultures are very relevant to the study of (indigenous) African philosophy – at least to the extent that both ethno-philosophy (philosophy based on cultural values and practices of a given society) and philosophic sagacity (philosophy as derived from sages in a given society) are still relevant. This gives a clear and imperative indication that discussions on what African philosophy is, or should be, cannot be devoid of culture. The mention of traditional cultures means that there are in Africa a variety of ethnic groups with cultures that vary or differ in several respects. Nevertheless, there are some underlying similarities that run through these cultures which justify speaking of an African traditional cultural heritage which has been preserved and passed down the generations. It is in respect of exhibiting this traditional culture that literalists have written insightful books. This paper concerned itself with one of the works of the renowned African writer, Chinua Achebe. His literary work, Things Fall Apart, just like the writings of other authors, presents philosophical elements in various forms, including; religion, proverbs, idioms, folk music, songs and folklores. Our aim, in this paper, was, primarily, to identify these indigenous African cultural traditions in Things Fall Apart and to draw out the elements of philosophy embedded in them.